ANALISIS MINAT KONSUMEN PADA PRODUK CV JAKARTA POWDER DRINK DENGAN MENGGUNAKAN METODE ASOSIASI ALGORITMA FP GROWTH - Novia Febrianty (2022)
CV Jakarta Powder Drink is a company that produces beverage powders that are used to make beverage products in various restaurants and shops that have distributed their products throughout Indonesia. The problem faced by the company is that there is an imbalance in sales of various product variants, making it difficult to make production and sales decisions. This problem can be solved if the company can understand consumer interest in the products being sold, because production and sales are closely related to consumer interest. This study aims to determine the pattern of consumer interest so that it can help companies both in making stock production management decisions and in making marketing strategies to increase sales. To be able to find out patterns of consumer interest, data mining techniques are used, namely associations using the FP Growth algorithm. This algorithm applies FP Tree generation in finding frequent itemset which can form association rules in the form of purchasing patterns. This study uses transaction data that contains 504 records. In this study, several experiments were carried out to see the number of association rules obtained with certain minimum support and minimum confidence values. Based on the comparison, used a minimum support value of 0.05 and a minimum confidence of 0.7 with good accuracy in mind, and obtained as many as 8 association rules which then can be used as the basis for strategic recommendations such as stock management, product placement and catalogs, recommendation features, and so on.